Wybrane składniki diety w profilaktyce najczęściej występujących nowotworów w Polsce - przegląd aktualnych wyników badań = Selected components of the diet in the prevention of the most common cancers in Poland - overview of current research results - Maciej Putowski; Marta Piróg; Olga Padała; Halina Piecewicz-Szczęsna; Walery Zukow (Kazimierz Wielki University, 2015)
Putowski Maciej, Piróg Marta, Padała Olga, Piecewicz-Szczęsna Halina, Zukow Walery. Wybrane składniki diety w profilaktyce najczęściej występujących nowotworów w Polsce - przegląd aktualnych wyników badań = Selected components of the diet in the prevention of the most common cancers in Poland - overview of current research results. Journal of Education, Health and Sport. 2015;5(8):73-84. ISSN 2391-8306. DOI 10.5281/zenodo.25591 http://dx.doi.org/10.5281/zenodo.25591 https://pbn.nauka.gov.pl/works/604079 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-b947908d-7e62-4767-8f2a-b637cb510dd3 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A73-84 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015.   Wybrane składniki diety w profilaktyce najczęściej występujących nowotworów w Polsce - przegląd aktualnych wyników badań = Selected components of the diet in the prevention of the most common cancers in Poland - overview of current research results   Maciej Putowski¹, Marta Piróg¹, Olga Padała¹, Halina Piecewicz‑Szczęsna², Walery Zukow3   ¹ Studenckie Koło Naukowe przy Katedrze i Zakładzie Epidemiologii, Katedra i Zakład Epidemiologii, UM w Lublinie ² Katedra i Zakład Epidemiologii, UM w Lublinie, ul. Chodźki 1 20-093 Lublin 3 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Abstrakt   W wielu zadaniach przypisanych profilaktyce chorób nowotworowych duże znaczenie ma właściwa dieta. Według ekspertów Światowej Fundacji Badań nad Rakiem korzystne zmiany w sposobie odżywiania mogłyby zapobiec większości zachorowań na raka okrężnicy i raka żołądka. Korzystne działanie w prewencji raka płuc wykazują karotenoidy, selen czy sulforafan, obecne w warzywach kapustowatych. Nowotwory jelita grubego zaliczane są do nowotworów dietozależnych, w związku z czym spożywanie wystarczających ilości błonnika, probiotyków, wapnia i witaminy D może znacznie obniżyć ryzyko zachorowania. Rak piersi jest najczęściej diagnozowaną chorobą nowotworową i drugą pod względem przyczyn zgonów kobiet w Polsce. Wyniki wielu badań wskazują na pozytywne działanie fitoestrogenów, sezaminy czy kurkuminy w zapobieganiu nowotworom sutka. Zapadalność na raka prostaty wśród Azjatów pijących codziennie napary z zielonej herbaty jest niższa w porównaniu z mieszkańcami państw zachodnich. Znane są też opracowania wskazujące na ochronne działanie owocu granatu. Proces onkogenezy w dużej mierze zależy od codziennych zwyczajów dietetycznych danej jednostki.   Abstract   The proper diet is essential in the prevention of cancer. According to the World Cancer Research Fund positive changes in a diet might prevent most of cases of colon cancer and gastric cancer. Carotenoids, selenium and sulforaphane, which is an ingredient of brassicaceae vegetables, present a beneficial effect in prevention of lung cancer.  Tumors of the large intestine are classified to cancers which are exceedingly related to the diet, therefore the adequate intake of roughage, probiotics, calcium and vitamin  D may significantly reduce the risk of the illness. Breast cancer is the most commonly diagnosed cancer and second cause of death among all cancers of women. The research confirms the positive effect of  phytoestrogens, sesamin and curcumin in breast cancer prevention. The incidence of prostate cancer among Asians who drink daily green tea is lower in comprarison with residents of western countries. Moreover, the protective effect of pomegranate is already known. The oncogenesis is a complicated process which greatly depends on the dietary habits.   Słowa kluczowe: profilaktyka, nowotwory, dieta, czynniki żywieniowe, chemoprewencja. Keywords: prevention, cancers, diet, nutritional factors, chemoprevention.